PENGARUH KOMBINASI BAKTERI ENDOFIT TERHADAP PERTUMBUHAN KOPI ARABIKA (Coffeae arabica L.) YANG TERSERANG Pratyenchus coffeae - Dian Ineke Damayanti; Iis Nur Asyiah; Mochammad Iqbal (saintifika, 2017)
Endophytic bacteria are the most preferred biological agents in the last period to control Pratylenchus coffeae parasitic nematodes in coffee plants Endophytic bacteria are able to control P. coffeae and increase plant growth. The results of the application of endophytic bacteria can be increased through a combination application. This study aims to determine the effect of a combination of endophytic bacterial isolates isolated from a coffee plantation from Kalibendo garden on the growth of Arabica coffee seedlings attacked by P. coffeae nematode. The study used isolates of endocytic bacteria Micrococcus luteus, Micrococcus sp. and Bacillus sp. the density of 109 cfu in two-month Arabica coffee plant seeds with 9 treatments, 4 replications and 3 sub-replication for 4 months of research. The results showed that a combination of endophytic bacterial isolates was able to significantly increase the growth of Arabica coffee plant seeds.